2016
DOI: 10.1117/12.2214598
|View full text |Cite
|
Sign up to set email alerts
|

Continuous analog of multiplicative algebraic reconstruction technique for computed tomography

Abstract: We propose a hybrid dynamical system as a continuous analog to the block-iterative multiplicative algebraic reconstruction technique (BI-MART), which is a well-known iterative image reconstruction algorithm for computed tomography. The hybrid system is described by a switched nonlinear system with a piecewise smooth vector field or differential equation and, for consistent inverse problems, the convergence of non-negatively constrained solutions to a globally stable equilibrium is guaranteed by the Lyapunov th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The second and third systems, which are respectively inspired by continuous analogs [19,22] of the multiplicative algebraic reconstruction technique [23,24] and the maximum-likelihood expectation-maximization [3,25] algorithm, are given by…”
Section: Dynamical Systemsmentioning
confidence: 99%
“…The second and third systems, which are respectively inspired by continuous analogs [19,22] of the multiplicative algebraic reconstruction technique [23,24] and the maximum-likelihood expectation-maximization [3,25] algorithm, are given by…”
Section: Dynamical Systemsmentioning
confidence: 99%
“…Reconstructed image pixels were obtained by using the initial value problem of differential equations describing the dynamical system, for example, a continuous-time image reconstruction (CIR) system. The proposed hybrid dynamical system has a different vector field from that of our previously presented continuous system [20][21][22]. We indicated that discretizing the differential equations using the geometric multiplicative 2 Mathematical Problems in Engineering first-order expansion of the nonlinear vector field leads to the exact same iterative formula of the power-based OS-EM with the scaling parameter as a step size of discretization.…”
Section: Introductionmentioning
confidence: 95%
“…Conventional methods for discrete tomography include the iterative reconstruction method involving an iterative algorithm and image segmentation [3], an optimization algorithm based on minimizing an energy function to discretize multiple intensity values [4], and various other methods [5][6][7][8]. In this paper, we propose a dynamical method based on the continuous-time optimization approach with nonlinear differential equations [9][10][11][12][13] that are capable of obtaining a desired tomographic image through convergence to a limit set of the differential equations. Our method utilizes the competition dynamics of generalized Lotka-Volterra systems [14] to solve the problem of multivalued discrete tomography.…”
Section: Introductionmentioning
confidence: 99%